In quest of 'other modes of being': J.M. Coetzee's ontological inquiries. Issue 3 (15th April 2016) - Tajiri, Yoshiki
Abstract : J.M. Coetzee's work is characterised by profound meditations on the question of being, though this aspect tends to be obscured by his ethical and political concerns. The characters of his novels are often faced with the fundamental question of why they (have to) exist in the way they do. Typically, Elizabeth Costello wonders, 'Are there other modes of being besides what we call the human into which we can enter; and if there are not, what does that say about us and our limitations?' This sense of the contingency of being human – the feeling that one could have been non-human – underlies Elizabeth Costello's (and Coetzee's) deep commitment to the lives of animals. This essay aims to illuminate such an ontological theme in Coetzee's work by offering a revaluation of In the Heart of the Country, in which it first substantially emerges, and then by outlining its developments in the recent works such as Elizabeth Costello, the 2006 lecture 'Eight Ways of Looking at Samuel Beckett', Here and Now and The Childhood of Jesus . In all these works, the human mode of being is questioned in relation to animals and relativised as something accidental. I will try to shed a new light on Coetzee's work by presenting him as a philosophical author concerned with the ontological questions regarding the mode of being.